2016
DOI: 10.1136/annrheumdis-2016-eular.3110
|View full text |Cite
|
Sign up to set email alerts
|

THU0587 Clinical Characterization of Castleman's Disease in A Group of Pediatric Patients

Abstract: BackgroundCastleman's disease (CD) is a rare lymphoprolipherative mostly benign disorder presenting in two major forms: localized (unicentric) and systemic (multicentric). Based on pathomorphological finding it is classified as hyaline-vascular, plasma cell or mixed type. The age of onset can differ greatly from infancy to adulthood. Except for lymph node hyperplasia, patients with CD can also develop such symptoms as anemia, fatigue, hepatosplenomegaly, low-grade fevers and other systemic symptoms.ObjectivesA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In the current study, the median age was 11.5 years (ranging from 4 -to 17 years). The majority was in males [5], and as in the current study. Unicentric CD (UCD) is most commonly found in the mediastinum [6], that was against the current study finding as unicentric disease had the upper hand of the study cases (75%) but Unicentric patients were presented with Lymphadenopathy either Cervical, supraclavicular, Axillary LN, 2 of them were having retroperitoneal and paravertebral soft tissue lesion and the rest had mediastinal masses.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, the median age was 11.5 years (ranging from 4 -to 17 years). The majority was in males [5], and as in the current study. Unicentric CD (UCD) is most commonly found in the mediastinum [6], that was against the current study finding as unicentric disease had the upper hand of the study cases (75%) but Unicentric patients were presented with Lymphadenopathy either Cervical, supraclavicular, Axillary LN, 2 of them were having retroperitoneal and paravertebral soft tissue lesion and the rest had mediastinal masses.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study there were only 12 pediatric patients with confirmed pathology as castleman disease between the periods from July 2007 till end of 2017. Age of onset varied from 0 to 16 years (median 8.5 years) [5]. In the current study, the median age was 11.5 years (ranging from 4 -to 17 years).…”
Section: Discussionmentioning
confidence: 51%